DEVELOPING A NEUROLOGY MENTORING PROGRAMME FOR TRAINEES. Issue 10 (9th September 2014) - Rohrer, Jonathan Daniel; Devine, Helen; Foulkes, Alexander; Johnston, Ann; Mallam, Beth; Marshall, Charles; Stanton, Biba; Thomas, Rhys; Blackburn, Daniel
Abstract : Background: The popularity of neurology compared with other medical specialities has declined in recent years, particularly in some parts of the country. Changes in medical school curricula and in junior doctor training mean that many doctors have less exposure to neurology than previously. To address this the ABN Trainees Committee have set up a national neurology mentoring programme, with the aim of supporting individuals who show an interest in neurology, enabling them to manage their career development in an effective manner. Objectives: 1) To provide a one-to-one mentor-mentee relationship between a neurology registrar and a junior doctor interested in a career in neurology; 2) To help mentees understand what they want from their career and to help them set goals for personal and professional development; 3) To help mentors understand their role in mentoring and provide appropriate training to allow them to fulfil their role. Plan: Mentors and mentees will be in contact via email with 1 or 2 face-to-face meetings per year. Mentors will be encouraged to invite mentees to local neurology rounds. A standardised feedback form will be used to qualitatively report outcomes of the programme.